Diary of a wimpy kid : the third wheel - Kinney, Jeff (New York : Amulet, 2012)
A Valentines Day dance at Gregs middle school has turned his world upside down until an unexpected twist gives Greg a partner for the dance and leaves his best friend Rowley the odd man out.
Keywords: Diaries-Fiction